Secured Authentication and Spam Filtering - Mat Khair, Azrulisham; Han, Lock Siew (Journal of Computing Technologies and Creative Content, 2019)
Webmail are one of the most popular platform for Sending and receiving emails using a web browser. The webmail has the capability of sending messages or receive message via internet which makes it almost cost free for the users to communicate with each other. Unfortunately, like any other webmail, majority of these applications are vulnerable to brute force attacks and have junk email problem at their webmail. The motivation for this thesis is the need to identifying security services of a Webmail and to design a secure Webmail system for user. This research approach which provides a secure Webmail design which protects its users with better integrity, confidentiality and privacy. To achieve this goal a research is conducted to investigate current security features of popular for webmail based on the latest solution. A list of requirements for good security is generated and based on those requirements an architecture is designed. A demo is also implemented and evaluated